Faktor yang Mempengaruhi Pertumbuhan Ekonomi Indonesia dengan Pendapatan Perkapita melalui Variabel Intervening - Vinka, Annisa; Sa'adati, Nila (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
This study aims to determine how the Effect of Investment, Labor Absorbers, and Zakat on Economic Growth with Per Capita Income as an Intervening Variable in Indonesia (2012-2022 Period). This study used quantitative methods with secondary data obtained through the website of related agencies. Data processing using the Eviews 9 application. Based on data analysis, it is produced that investment has a significant positive effect on economic growth, employment has a positive insignificant effect on economic growth, zakat has a positive insignificant effect on economic growth, per capita income has a negative insignificant effect on economic growth. Using the sobel test, it was produced that there is an intervening influence of investment variables on economic growth through per capita income, there is an intervening influence of labor absorption variables on economic growth through per capita income, there is no intervening influence of zakat variables on economic growth through per capita income. Simultaneously, all variables have a positive and significant effect on economic growth.